IMPLEMENTATION OF A SMART HOME BASED ON INTERNET OF THINGS USING CISCO PACKET TRACER - Sinaga, Dedi Candro Parulian; Tampubolon, Gunung Juanda; Ndruru, Ifanlius (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
A smart home is a home that uses information and communication technology, especially the Internet of Things (IoT), to increase comfort, efficiency, security and energy management. The main idea of ??a smart home is to connect various electronic devices and systems in the house so that they can interact with each other and with the occupants of the house automatically or through centralized control. Users can control devices in the home remotely via mobile devices or computers. This allows them to regulate the temperature, check home security, or control equipment even when they are not at home. Smart homes are often equipped with sophisticated security systems, including security cameras, motion sensors, and alarms. Residents can monitor and control this system via their smart devices. Smart homes can be a practical and innovative solution to improve the quality of life and optimize home management. However, it is important to consider the security and privacy issues as well as the costs associated with using this technology. Using this smart home really helps users to carry out activities calmly outside the home because it can monitor the electrical conditions at home. The device used to create a smart home simulation is using Cisco Packet Tracer.